Prevalence of chemotherapy-induced anemia and its impact on quality of life in breast cancer patients - Ramsha Batool; Tehreem Hayat; Hira Rizwan Butt; Fatima Um Ul Baneen; Hooria Fayyaz; Tayyaba Rafiq; Mehrulnisa Akhtar; Uswa Fayyaz; Maria Ahmed; Ayesha Azeem; Mah Gul Khan; Mahnoor Ikram Khan; et al. (Journal of Complementary and Integrative Medicine, 2026)
Abstract Background Chemotherapy-induced anemia (CIA) is a frequent condition among breast cancer patients who are treated with systemic chemotherapy, and is linked to fatigue, decreased functional capacity, and poor quality of life. Objectives To determine the prevalence of chemotherapy-induced anaemia and evaluate its impact on the quality of life of breast cancer patients receiving chemotherapy. Methods This cross-sectional study was performed at the Ghurki Trust Teaching Hospital in Lahore, Pakistan, from January 2024 to April 2025. The trial included 100 female patients with histopathologically confirmed breast cancer who had received a minimum of three treatment cycles. Anaemia was determined using World Health Organization guidelines (Hb